Respostas
respondido por:
0
( x + 2 ) ! = 72 . x !
( x + 2 ).(x + 1) . x! = 72 . x !
( x + 2 ).(x + 1) = (72 . x!)/x!
( x + 2 ).(x + 1) = 72
x² + 3x + 2 - 72 = 0
x² + 3x - 70 = 0
Δ = 3²-4.1.(-70)
Δ = 9 + 280
Δ = 289
x' = (-3+√289)/(2 . 1)
x' = (-3+17)/2
x' = 14/2
x' = 7
x'' = (-3-√289)/(2 . 1)
x'' = (-3-17)/2
x'' = -20/2
x'' = -10
Descartamos x'', já que isso nos retornaria fatorial de numero negativo, logo a resposta é x=7
Perguntas similares
3 anos atrás
3 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás